Ekonomi Politik dan Lingkungan Hidup - Putri, Bella Kharisma; Magriasti, Lince (Lembaga Yasin AlSys, 2024)
The aim of writing this article is to look at Political Economy and the Environment. The environment is everything that exists around humans and is in a reciprocal relationship. The living environment is a system that is a spatial unity between living things and other abiotic components. The interaction between the natural environment and its surroundings forms an ecological system (ecosystem). The environment plays a role as a habitat for living creatures on earth. Environmental components consist of two types, namely: Biotic components, living creatures which include animals, plants and humans. Abiotic components are non-living objects, including water, soil, rocks, air and sunlight. The data collection technique for this research is a library research library study sourced from various reading literature and previous research articles on Political Economy and the Environment. . The expansion of oil palm plantations in forest areas also has an impact on changes in the ecological landscape and changes in land use, changes in land cover as well as several serious environmental problems such as depletion of soil nutrients and increased carbon emissions due to deforestation and emissions inherent in the processing of oil palm fruit.